2020
DOI: 10.3390/rs12101670
|View full text |Cite
|
Sign up to set email alerts
|

BDD-Net: A General Protocol for Mapping Buildings Damaged by a Wide Range of Disasters Based on Satellite Imagery

Abstract: The timely and accurate recognition of damage to buildings after destructive disasters is one of the most important post-event responses. Due to the complex and dangerous situations in affected areas, field surveys of post-disaster conditions are not always feasible. The use of satellite imagery for disaster assessment can overcome this problem. However, the textural and contextual features of post-event satellite images vary with disaster types, which makes it difficult to use models that have been developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Specifically, a mathematical formula for the effective number of samples in [37] was adopted, which preferred to assign higher weights to changed pixels' loss. Focal loss was combined to form the final effective sample number adaptively weighted loss (EAWLoss), which confirmed the effectiveness of the pixel-level binary classification task and can be extended to a multiclass task such as semantic change detection [38][39][40].…”
Section: Attention Mechanismmentioning
confidence: 94%
See 1 more Smart Citation
“…Specifically, a mathematical formula for the effective number of samples in [37] was adopted, which preferred to assign higher weights to changed pixels' loss. Focal loss was combined to form the final effective sample number adaptively weighted loss (EAWLoss), which confirmed the effectiveness of the pixel-level binary classification task and can be extended to a multiclass task such as semantic change detection [38][39][40].…”
Section: Attention Mechanismmentioning
confidence: 94%
“…Specifically, a mathematical formula for the effective number of samples in [37] was adopted, which preferred to assign higher weights to changed pixels' loss. Focal loss was combined to form the final effective sample number adaptively weighted loss (EAWLoss), which confirmed the effectiveness of the pixel-level binary classification task and can be extended to a multiclass task such as semantic change detection [38][39][40]. Our contributions can be summarized as follows: (1) We proposed a novel end-to-end framework called a multi-level change contextual refinement net (MCCRNet) for the change detection of bi-temporal remote sensing images.…”
Section: Attention Mechanismmentioning
confidence: 98%
“…Other researchers adopted satellite images to examine damage status over a larger scope of work (i.e. multiple buildings at the community level) after natural disasters such as flood, earthquake, volcanic eruption, hurricane and wildfire [222,223].…”
Section: (D) Computer Vision Inverse Problems In Shmmentioning
confidence: 99%
“…Many researchers [40][41][42][43] began to use the xBD dataset as benchmark dataset for automated building damage assessment studies. Shao et al [41] reported a new endto-end remote sensing pixel-classification CNN to classify each pixel of a post-disaster image as an undamaged building, damaged building, or background.…”
Section: Related Workmentioning
confidence: 99%
“…Many researchers [40][41][42][43] began to use the xBD dataset as benchmark dataset for automated building damage assessment studies. Shao et al [41] reported a new endto-end remote sensing pixel-classification CNN to classify each pixel of a post-disaster image as an undamaged building, damaged building, or background. During the training, both pre-and post-disaster images were used as inputs to increase semantic information, while the dice loss and focal loss functions were combined to optimize the model for solving the imbalance problem.…”
Section: Related Workmentioning
confidence: 99%